PERBANDINGAN KARAKTERISTIK PENCAIRAN BATUBARA BANKO DAN TANITO HARUM SEBAGAI EFEK KERJA KATALIS LOGAM TRANSISI - Hanif, Muhammad; Adiarso, Adiarso (Jurnal Energi dan Lingkungan (Enerlink), 2008)
Characterization of two oil derived from Indonesian lower-rank coals from SouthBanko (SB) and Tanito Harum (TH) were carried out after liquefied in thepresence of nickel/molybdenum (Ni/Mo) and cobalt/ molybdenum (Co/Mo)catalysts without added solvent. Both coals treated with Ni/Mo have highconversion than those treated with Co/Mo when reacted with hydrogen withinitial pressure of 6MPa at 400oC for 30 minutes. However, with sulfur (CS2)added, the difference between Ni/Mo and Co/Mo catalysts for conversion of bothcoals is eliminated. SB-coal exhibits better conversion than that of Ni/Mo orCo/Mo-treated TH-coal. This probably due to the structure of TH coal is morecondensed and stronger than that of SB coal. The effect of single metal (Ni, Coor Mo separately) could explain the different conversion between Ni/Mo andCo/Mo with and without sulfur and also the difference between SB and TH whenthey reacted with Ni/Mo and Co/Mo with and without added sulfur. The order ofeffectiveness for SB, when it reacted in the absence of sulfur, was decreasedfrom Ni>Mo>Co. But the order was shifted to Mo>>Ni>Co. The similar order wasalso found for TH coal under the same conditions. The study also shows thatreactivity of SB coal was higher than that of TH coal. This results in better yield offuels. Fortunately, the TH coal is still potentially developed for introducing theefficient process of sub bituminous coal liquefaction in Indonesia.Kata Kunci: coal liquefaction, katalis Ni/Mo, Banko, Tanito Harum